The Prospects For Normalization Between Morocco And Israel Under King Mohammed Vi - Shallal Abbas, Faisal; Kamil Hamzah, Majeed; Abid Esmael, Ahmed (Opción, 2019)
The relations between Morocco and Israel are important in the field of international relations because of the nature of the relationship. Since King Mohammed VI ascended the throne in Morocco, he contributed directly to maintaining relations between the capitals of the two countries. These relations did not break even at the height of the Arab-Israeli conflict. The decline according to regional data is a long history of communications varied in degree between confidentiality and public, as indicated by many previous studies (1). Based on the above, it can be said that the Moroccan-Israeli relations transcend the political and strategic dimensions of any bilateral relations between the coun- tries, since their nature makes them directly affect the reality of the Magh- reb region. The premise of the study stems from the fundamental point that the accession of King Mohammed VI to the throne in 1999 He contributed to building relations with all countries for a lasting peace in the Arab region and Israel is one of the countries with which the Moroccan government established high-level relations that reach the level of normalization in all political, eco- nomic, security and cultural fields in order to ensure Israel stands by Morocco as a market for its goods and a key pillar in North Africa to ensure its move- ment on the African continent based on fraternal relations.